2007
DOI: 10.1089/ars.2006.1519
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-Mediated Induction of Heme Oxygenase Type I and Carbon Monoxide Release from Astrocytes Protects Nearby Cerebral Neurons from Hypoxia-Mediated Apoptosis

Abstract: To study a putative paracellular protective mechanism of astrocytes for neurons, immunohistochemical analysis was performed in ischemic rat brain, which colocalized with the expression of heme oxygase-1 (HO- 1) in astroglias surrounding dying TUNEL-positive neurons. As an in vitro paradigm for ischemia, cultured astrocytes were exposed to normobaric hypoxia (pO(2) asymptotically equal to 10 torr), which triggered marked increase in the expression of a 33 kDa stress protein, identified as HO-1. Induction of HO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…Thus, systemically administered CO to the brain, elicits vasodilator and cytoprotective effects in the cerebral circulation, has no long-term adverse effects, and protects the neonatal brain from cerebral vascular injury caused by epileptic seizures [41]. In cultured cerebral neurons CO decelerated hypoxiamediated apoptosis by lowering the activity of caspase-3 in a cGMP dependent manner [42]. Regarding inflammation, CO blocked TNF--and glutamate-induced reactive oxygen species accumulation and apoptosis in newborn pig cerebral microvascular endothelial cells [43,44].…”
Section: A Carbon Monoxidementioning
confidence: 99%
“…Thus, systemically administered CO to the brain, elicits vasodilator and cytoprotective effects in the cerebral circulation, has no long-term adverse effects, and protects the neonatal brain from cerebral vascular injury caused by epileptic seizures [41]. In cultured cerebral neurons CO decelerated hypoxiamediated apoptosis by lowering the activity of caspase-3 in a cGMP dependent manner [42]. Regarding inflammation, CO blocked TNF--and glutamate-induced reactive oxygen species accumulation and apoptosis in newborn pig cerebral microvascular endothelial cells [43,44].…”
Section: A Carbon Monoxidementioning
confidence: 99%
“…The reaction catalyzed by HO is also the main source of CO in mammals, with $85% of the CO produced under normal physiological conditions being derived from heme. There has been increasing evidence of the cellular regulatory actions of CO including anti-inflammatory, antiapoptotic, antiproliferative, and vasodilatory effects [7][8][9][10]. Many of the effects of CO involve the increased synthesis of cyclic guanosine monophosphate (cGMP) by way of its activation of soluble guanylate cyclase (sGC) [11,12], activation of mitogen-activated protein kinase (MAPK) signaling pathways [13][14][15][16], and stimulation of calciumdependent potassium channels [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, astrocytes are also efficient in decreasing ATP consumption when oxygen- and glucose-deprived (Yager et al, 1994). All these traits of astrocytic adaptation to low oxygen tensions presumably contribute to their role in safeguarding neurons from detrimental effects of anoxia and hypoxia (Vibulsreth et al, 1987; Imuta et al, 2007). Previous studies have demonstrated that after ischemic insult neurons fail to survive if neighboring astrocytes are not viable (Takano et al, 2009).…”
Section: Effects Of Hypoxia On Neurons and Astrocytesmentioning
confidence: 99%